2015
DOI: 10.1037/xhp0000119
|View full text |Cite
|
Sign up to set email alerts
|

The vista paradox: Framing or contrast?

Abstract: The vista paradox is the illusion in which an object seen through a window appears to shrink in apparent size (and appears farther away) as the observer approaches the window. Paradoxically, the distal object appears smaller as its visual angle increases. We investigated the effect in four experiments varying object size, distance, point of fixation, and texture of the frame and of the object. In the first experiment, we tried to confirm the illusion and to test the robustness of the phenomenon. In the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
(34 reference statements)
0
8
3
Order By: Relevance
“…More experimental studies are surely needed to explicitly test the validity of the alternative explanation for both the vista paradox and the size inflation obtained in this study. For one thing, experiencing the vista paradox relies on the viewer to move from a more distant viewing location to a nearer one (Daum et al, 2015), while the reduction in size inflation obtained in this study does not. Consequently, what was found about the vista paradox may not apply to the mirror image inflation.…”
Section: The Dependency Of Size-constancy On Distribution and Kind Ofcontrasting
confidence: 62%
See 1 more Smart Citation
“…More experimental studies are surely needed to explicitly test the validity of the alternative explanation for both the vista paradox and the size inflation obtained in this study. For one thing, experiencing the vista paradox relies on the viewer to move from a more distant viewing location to a nearer one (Daum et al, 2015), while the reduction in size inflation obtained in this study does not. Consequently, what was found about the vista paradox may not apply to the mirror image inflation.…”
Section: The Dependency Of Size-constancy On Distribution and Kind Ofcontrasting
confidence: 62%
“…This alternative explanation is consistent with what has been known about the vista paradox (Walker et al, 1989), an illusion in which an object seen through a window appears to shrink in apparent size (and appears father away) as the observer approaches the window. Daum et al (2015) found that the illusion requires the observer to keep fixating on the window frame or a location other than that of the target. Fixating on the window frame while paying attention to an object within the window suggests a form of attention on the target-window proportion, a pictorial relationship that defines the vista in question.…”
Section: The Dependency Of Size-constancy On Distribution and Kind Ofmentioning
confidence: 99%
“…In the first two studies discussed in this article, we focused on a large-scale architectonical setting in which it is possible to experience a magnificent instance of the vista paradox. Previous studies (Daum et al., 2015; Walker et al., 1989) explored the phenomenon considering a 3 - to 3.5 -m distance between the observer and the frame, while in our case, we could assess the illusion on a length of 162.2 m. We observed a nonlinear trend in both the experimental and control conditions. The perceived change in size as a function of distance was emphasized in the first meters near the object.…”
Section: Discussionmentioning
confidence: 61%
“…Reinhardt-Rutland (1990) tried to explain the vista paradox with the effect of induced movement, while Daum, Both, Bertamini, and Hecht (2015) have investigated the illusion in a laboratory setting including a 3 -m corridor, a 20 × 20 cm aperture, and a target object represented by a cube of two sizes: 10 × 10 cm and 14 × 14 cm. The cube was positioned at three possible distances from the aperture: 135, 270, and 405 cm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation